Characteristics of the water cycle of Jinan karst spring in northern China. Issue 7 (7th July 2022) - Deng, Xing; Xing, Liting; Yu, Miao; Zhao, Zhenhua; Li, Changsuo; Su, Qingwei
Abstract: Due to the multi-scale nature and complexity of the flow field, it has always been difficult for hydrogeologists to accurately grasp the water cycle characteristics of the karst water flow system. The inverse statistical model and IsoSource model were employed to calculate the spring age and the mixing ratio of spring recharge sources of the four large spring groups in Jinan. The karst hierarchical groundwater flow system was identified based on multiple factors. We found that the groundwater ages of Baotu Spring and Heihu Spring are about 6a–10a, and those of Wulongtan Spring and Pearl Spring are about 30a–35a. The main recharge sources of spring water of the four large spring groups were recognized as artificial recharge water, Ordovician karst water, and Cambrian Zhangxia Formation karst water. There were distinct differences in the recharge proportion of the four large spring groups. Three groundwater flow systems were identified according to multiple factors, which were local, intermediate, and regional. Furthermore, different levels of groundwater flow systems were recharged to the four large spring groups in different proportions. The research results provided new insights into the analysis of the hierarchical cycle and evolution of karst water. HIGHLIGHTS: The spring age of the four large spring groups is corrected by ISM model. The IsoSource model is used to calculate the mixing ratios of recharging water sources of the four large spring groups. Identify the karst hierarchical groundwater flow system in Jinan spring domain by combining multiple factors.